Pseudo-Reorganization of Language Cortical Function at fMR Imaging: A Consequence of Tumor-Induced Neurovascular Uncoupling - Ulmer, John L.; Krouwer, Hendrikus G.; Mueller, Wade M.; Ugurel, M.Sahin; Kocak, Mehmet; Mark, Leighton P. (American Journal of Neuroradiology, 2003)
Summary: A left-handed patient with a grade II left frontal lobe astrocytoma had spontaneous seizures causing speech arrest and uncontrolled right upper extremity movements. Word-generation functional MR (fMR) imaging showed activity nearly exclusively in the right inferior frontal gyrus. The clinical history of the speech arrest and the intraoperative mapping proved left-hemisphere language dominance. Tumor involvement of the left inferior frontal gyrus caused uncoupling of the blood oxygenation level‐dependent (BOLD) and neuronal response, leading to the erroneous fMR imaging appearance of right-hemisphere language dominance. Discrepancies between BOLD and intraoperative mapping in areas near lesions illustrate the complementary nature of these techniques.